Efektivitas Model PjBL untuk Keterampilan Analitis Mahasiswa dalam Penelitian Kuantitatif: Pendekatan Eksperimen - Pratama, Robin; Aprillitzavivayarti, Aprillitzavivayarti (SAP (Susunan Artikel Pendidikan), 2024)
This research is motivated by the low analytical skills of students in quantitative research, especially among those with low initial ability levels. The study aims to evaluate the effectiveness of the Project-Based Learning (PjBL) model in enhancing students' analytical skills in quantitative research. The research was conducted on students enrolled in the quantitative research methods course during the 2023/2024 academic year in the Educational Administration Study Program at FKIP Universitas Jambi. The research methodology employed a Quasi-Experimental quantitative analysis. The results indicate that PjBL has a significantly positive impact on students' understanding and application of methodological concepts in research projects. Policy recommendations include integrating PjBL into the Quantitative Research Methods curriculum, training lecturers and teaching staff, developing relevant learning materials, and providing supportive facilities and resources. Continuous evaluation of PjBL implementation and dissemination of results and best practices are crucial to strengthening learning effectiveness. With these recommendations, it is expected that students will be better prepared to meet the increasingly complex demands of the workforce, equipped with strong analytical skills and the ability to independently apply quantitative research concepts.